Pengaruh Pendidikan Kewirausahaan, Motivasi Berprestasi, dan Lingkungan Sosial terhadap Intensi Berwirausaha Mahasiswa FKIP UNS Angkatan 2019 - Eka Nur Hidayati; Trisno Martono; Sudarno Sudarno (Journal on Education, 2024)
The purpose of this study was to determine 1) the effect of entrepreneurship education on entrepreneurial intention of FKIP UNS students class of 2019; 2) the effect of achievement motivation on entrepreneurial intention of FKIP UNS students class of 2019; 3) the effect of social environment on entrepreneurial intention of FKIP UNS students class of 2019; 4) the effect of entrepreneurship education, achievement motivation, and social environment on entrepreneurial intention of FKIP UNS students class of 2019. This research is a quantitative study with a population of the FKIP UNS class of 2019. The sampling technique used Proportionate Random Sampling with a sample size of 322 respondents. Data collection techniques using questionnaires and data analysis using multiple linear regression analysis. The results showed that 1) there is a positive and significant effect of entrepreneurship education on entrepreneurial intention of FKIP UNS students class of 2019; 2) there is a positive and significant effect of achievement motivation on entrepreneurial intention of FKIP UNS students class of 2019; 3) there is a positive and significant effect of social environment on entrepreneurial intention of FKIP UNS students class of 2019; 4) there is a positive and significant effect of entrepreneurship education, achievement motivation, and social environment on entrepreneurial intention of FKIP UNS students class of 2019.